Development of halal hydrolysates-based nanocosmeceutical formulation from Actinopyga lecanora - Bahari, Aqilah Noor (2021)
Actinopyga lecanora is classified among the edible species of sea cucumber. Its hydrolysates, which obtained from enzymatic hydrolysis was reported to contain relatively high antioxidant activities, mostly applied in food industries. Actinopyga lecanora hydrolysates (ALH) is halal depending on its source (marine animal), extraction process and the safety measurement. Even though ALH have high potential of antioxidant activities, which is essential in skin care products, no work has been reported specifically on ALH as an actives ingredient. Likewise, no related antityrosinase activity of ALH has been recorded. Therefore, to diversify the usage of ALH in the cosmeceutical application, nanoemulsion containing ALH was developed, particularly to alleviate skin aging and to improve skin pigmentation. This research consists of two parts; Part A is the optimization of hydrolysis conditions of ALH, while Part B covers the formulation of nanoemulsion containing ALH obtained from Part A. In Part A, ALH was hydrolysed from raw sample of Actinopyga lecanora using papain enzyme. The best conditions selected from the optimization were at pH 5.00, 70°C of reaction temperature, 9 h of hydrolysis time and 1.00% E/S ratio with the ALH having 55.00% of DH, 46.30% of DPPH radical scavenging activity and 108.20 Fe2+μg/mL of FRAP activity. The amount of hydrophobic amino acid (286.40 mg/g sample) was higher than hydrophilic amino acid (253.60 mg/g sample), indicated that the hydrophobic amino acid was responsible for the antioxidant and antityrosinase activities. SEM image of ALH pictured a smooth structures with pores as the protein was degraded into smaller peptides. In Part B, nanoemulsion formulation containing ALH was optimized using Doptimal mixture design. The optimum compositions were at 10.00% of safflower oil: argan oil (ratio 9:1), 1.00% of ALH, 13.75% of Tween 80: Span 80 (ratio 8:2) surfactants, 0.87% of xanthan gum, 73.69 % of water and 0.70% of phenonip. The actual particle size obtained was 139.80 nm, with the acceptable polydispersity index (0.302) and zeta potential (-27.50 mV). High conductivity of the nanoemulsion was observed (1311 μS/cm) with pH 5.38 and displayed a pseudoplastic behaviour. Morphology analysis disclosed a spherical shape of the nanoemulsion particles, monodispersed without any aggregation. Moreover, the nanoemulsion showed good stability within 28 days when stored separately at different temperatures (4 and 25°C). However, for long term storage, the suggested storage condition was at 4°C due to the unchanged of physical appearances (colour and odour) after 28 days. In vitro permeation study revealed that the permeability of ALH was improved to 66.48% of ALH released after 8 h of application. The kinetic released of ALH followed first-order model, in which the released was based on the concentrationgradient pattern. In vitro cytotoxicity test of all samples against normal 3T3 fibroblast cell recorded IC50 values more than 500 μg/mL, proved that the optimized nanoemulsion is safe, halal and suitable for topical application. Apart from that, an improved in antioxidant activity was shown after incorporating ALH to the nanoemulsion. The DPPH radical scavenging activity of nanoemulsion containing ALH had a significant difference (p<0.05) at concentration of more than 5000 μg/ml compared to the blank nanoemulsion. The FRAP activity of both samples also showed a significant difference (p<0.05) at every sample concentration. Similar pattern was found for antityrosinase activity whereby the optimized nanoemulsion containing ALH displayed a significant difference (p<0.05) in tyrosinase inhibition activities for both substrates, L-DOPA (43.20%) and L-tyrosine (46.60%). Overall, the nanoemulsion containing halal hydrolysates from A. lecanora was successfully formulated and have a full potential to be applied in cosmeceutical industries.